Oral Delivery of Lactococcus lactis Expressing Full-Length S Protein via Alginate–Chitosan Capsules Induces Immune Protection Against PEDV Infection in Mice - Miaoyan Yang; Denglong Xie; Wei Ji; Shu Jeffrey Zhu; Yongqi Zhou (Vaccines)
Background/Objectives: Porcine epidemic diarrhea (PED) is a highly contagious enteric infectious disease that causes severe morbidity and mortality in piglets, posing significant economic losses to the swine industry worldwide. Oral vaccines based on Lactococcus lactis offer a promising approach due to their safety and genetic manipulability. This study aims to develop and evaluate an oral L. lactis-based vaccine expressing the full-length PEDV S protein. Methods: A recombinant L. lactis strain expressing the PEDV S protein was constructed and encapsulated in alginate–chitosan microcapsules. Vaccine stability was tested in simulated digestive fluids, and mice were orally immunized. Immune responses were evaluated by measuring specific antibodies, cytokines, and lymphocyte proliferation. Results: The recombinant L. lactis NZ3900/pNZ8149-S strain successfully expressed the full-length PEDV S protein and maintained stable plasmid inheritance. Oral immunization in mice induced detectable PEDV-specific immune responses. Both encapsulated and non-encapsulated vaccines stimulated the production of IgG and sIgA antibodies, as well as cytokines associated with Th1 and Th2 responses. Notably, encapsulation with alginate–chitosan significantly enhanced bacterial survival in digestive conditions and further amplified immune responses, including higher antibody titers, elevated levels of IFN-γ, IL-4, and IL-10, and greater lymphocyte proliferation, indicating improved immune memory. Conclusions: The oral L. lactis NZ3900/pNZ8149-S vaccine expressing the PEDV S protein effectively induced systemic and mucosal immunity in mice. Encapsulation with alginate–chitosan further enhanced its immunogenicity and stability in gastrointestinal conditions. These results suggest that both the engineered L. lactis strain and the encapsulation strategy contribute to the development of a promising oral vaccine platform for controlling PEDV in swine populations.